Age-estimate evidence for a complex Middle to Late Pleistocene fluvial terrace aggradation spanning more than a 100-kyr interglacial–glacial cycle at Sutton Cross, eastern England. Issue 6 (December 2020) - Langford, H.E.; Griffiths, H.; Horne, D.J.; Keen, D.H.; Penkman, K.E.H.
Abstract: At Sutton Cross, eastern England, an undated River Nene 2nd Terrace was known to record a complex sequence of late Middle to Upper Pleistocene deposits. Amino acid geochronology was carried out for samples from four separate facies associations in order to provide a chronostratigraphic framework for this complex deposit. Each sample comprised three specimens of Bithynia tentaculata opercula. The intracrystalline protein decomposition results confirmed the sedimentary stratigraphic interpretation previously proposed for the site, i.e ., that fossiliferous sediments yielding fully temperate Mollusca and Ostracoda faunas are equivalent in age to marine isotope stage (MIS) 7. Palaeotemperature reconstructions based on the Ostracoda fauna (July: +14 to +26 °C; January: −4 to +5/+3 °C) embrace those of today at this location (July: +17 °C; January +3 °C). The sedimentary succession at Sutton Cross comprises vertically aggraded packages with a probable maximum age of MIS 8 and minimum age of MIS 2. This aggradation pattern (and age range) is also common to downstream sedimentary successions at Whittlesey, and is counterintuitive to the traditional terrace stratigraphy approach that expects laterally aggrading downstepping packages. The preservation of sediments of MIS 7 age and older at Sutton Cross with no evidence of glacial overriding places constraints on recently proposed late Middle Pleistocene regional ice limits.